EP955 Interval debulking surgery for advanced ovarian cancer in elderly patients (≥70 y): does the age matter?. (1st November 2019) - Pinelli, C; Morotti, M; Casarin, J; Tozzi, R; Ghezzi, F; Alazzam, M; Soleymani Majd, H
Abstract : Introduction/Background: Elderly ovarian cancer (OC) patients are more likely to be managed suboptimally and experience worse clinical outcomes as a result. Strategies to improve outcomes in this patients are lacking. Methodology: Retrospective analysis for consecutive patients with advanced stage OC (IIIC–IV) who were managed in Oxford University Hospital between January 2016 and July 2018 were analysed. All patients underwent neoadjuvant chemotherapy (NACT) and interval debulking surgery (IDS) according to our institution protocol. We divided the patients into two groups: an 'older group' (age ≥70 years) (Group 1) and a 'younger group' (age <70 years) (Group 2). The primary outcome of the study was the assessment of peri-operative morbidity amongst the two groups. Results: A total of 153 patients were referred during the study period. 114 patients underwent IDS after NACT (74.5%), of which 46 in Group 1 and 68 in Group 2. Elderly patients were more likely to receive more than three cycles of NACT prior to IDS when compared to younger patients (39% vs. 19%, p=0.03). Elderly patients were more frequently subjected to Cardiopulmonary Exercise Testing (CPET) as part of their pre-operative assessment (63% vs. 27%, p=0.002). For those who underwent IDS; optimal/complete resection was achieved in all patients in Group 1 (100%) and in 97% of patients in Group 2. With the exception of higher postoperative cardiac arrhythmias in Group 1 (11% vs. 1%, p=0.04), no significant differences in 30-day morbidity were observed. No 90-day death in both groups was registered. Conclusion: Older age should not preclude clinicians from offering ultra-radical resection, for patients with advanced OC who underwent careful preoperative assessment. In our series, elderly patients received the same treatment with similar outcomes to the younger group. CPET has an important role and clinicians should be encouraged to use it more frequently especially when ultraradical surgery is postponed. Disclosure: Nothing to disclose.